The Non-Sovereign Self, Responsibility, and Otherness Hannah Arendt, Judith Butler, and Stanley Cavell on Moral Philosophy and Political Agency - Kelz, Rosine; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
Drawing on Hannah Arendt, Judith Butler and Stanley Cavell, this book addresses contemporary theoretical and political debates in a broader comparative perspective and rearticulates the relationship between ethics and politics by highlighting those who are currently excluded from our notions of political community.
Keywords: Political science; Political theory; World politics; Ethics; Political philosophy; Social sciences -- Philosophy; Sociology; Political Science and International Relations; Political Theory; Political Philosophy; Social Philosophy; Sociology, general; Ethics; Political History; Electronic books